KOMPARASI SINKRONISASI FILE ANTARA METODE MOBILE AGENT DAN METODE PEER-TO-PEER - Wildana, Faiq (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
Good server has high availability, rapid response in addressing a number of the user according to his ability. Servers often run into problems so that the data might be inconsistent, and even data loss happen. The use of more than one server can be an alternative, either virtually or physically for the distribution of resources and reserves data. File synchronization is done to overcome it. Comparative research with quantitative approach aims to compare between mobile agent in the method of synchronizing files and to peer-to-peer application in performing file transfers. The peer-to-peer act as media to synchronize file. The literature study shows that this method of mobile agent as well as peer-to-peer have the same advantages. The results showed that the theoretical (literature) file synchronization methods can be implemented using a combination of mobile agent and peer-to-peer. In which the mobile agent is used as files change information carrier and used as a automation synchronization. Then the file transfer function is handled by the transfer files method adapt to Bit Torrent way. So that the synchronization speed can be improved. But there is a significant difference in the speed of the data comparison of both methods. In theory supposed to transfer files using peer-to-peer faster. From the results of this research can be done further engineering synchronize files using a combination of mobile agent and peer-to-peer, so that the results of the research can be proved definitely more precise.